Volar Percutaneous Screw Fixation for Scaphoid Nonunion - Gurger, M.; Yilmaz, M.; Yilmaz, E.; Altun, S. (Medknow Publications & Media Pvt Ltd, 2018)
Background: Percutaneous screw fixation is widely used in acute fractures of the scaphoid. In this study, we aimed to present our results with volar percutaneous screw fixation in patients with scaphoid nonunions. Methodology: A total of 12 patients with scaphoid nonunion (>= 13 weeks) that underwent volar percutaneous screw fixation were evaluated retrospectively. Two of the patients were female, and 10 were male. Mean age was 27 years (range = 19-41). The mean time that elapsed between the fracture and surgical procedure was 7.5 months (range = 4-12). According to the anatomic location, 33.3% were proximal pole, and 67.7% were waist fractures. All of the patients underwent percutaneous fixation with a headless cannulated screw from volar part under fluoroscopic guidance. Clinical evaluation was performed according to the modified mayo wrist scoring system (MMWS). The absence of a radiolucent fracture line on the radiographs was considered union on radiological evaluation. Results: The mean follow-up time was 18 weeks (range = 8-36). Union was achieved in all patients (91.6%), except one. The mean time to union was 15.5 weeks (range = 8-30). Based on MMWS system, 8 patients were interpreted as excellent, 3 patients as good. Conclusion: Percutaneous fixation in appropriate patients provides satisfactory results with high union and minimal complication rates in scaphoid nonunions.
Keywords: Nonunion; percutaneous fixation; scaphoid; volar